Blood pressure in acute ischemic stroke: challenges in trial interpretation and clinical management: position of the ESH Working Group on Hypertension and the Brain - Gąsecki, Dariusz (2018)
Altered blood pressure (BP) is a common phenomenon in acute ischemic stroke (AIS), with high BP being the most frequent scenario. The pathophysiology of BP changes in AIS is complex and only partially understood. The available evidence indicates that extremely high BP during AIS is associated with a poor outcome. Importantly, the observed relationship between BP and stroke outcome may or may not be causally related. Higher baseline BPs in focal cerebral ischemia may indicate preexisting hypertension, but may also be an effect of both nonspecific and stroke-related factors. Although antihypertensive therapy effectively reduces BP in AIS, studies on early BP lowering in AIS produce conflicting results in terms of functional outcome and mortality. Systematic reviews on BP management in AIS did not result in clinically applicable conclusions in general. However, the investigation on the effect of BP and its alterations in AIS are hampered by various important methodological issues. This position statement was prepared by a group of experts from the European Society of Hypertension and invited neurologists to discuss the main reasons for the discrepancies in the current evidence on the prognosis and treatment of altered BP in AIS which should be taken into account in future studies.